Stress and failure analysis of the crankshaft of diesel engine. (December 2017) - Witek, Lucjan; Sikora, Michał; Stachowicz, Feliks; Trzepiecinski, Tomasz
Abstract: In this work the failure analysis of the crankshaft of diesel engine was performed. Visual examination of the crankshaft fracture showed that beach marks, typical for fatigue failure were observed. Additional observations of the crack initiation zone indicated that crack origin was not covered by material defects or corrosion products. Performed hardness test of the fractured crank pin showed that large HRC values were observed in central part of the pin only. On the corner of cylindrical pin surface where the crack origin was located the hardness of material was much smaller. In order to explain the reason of premature crankshaft damage, the finite element method was utilized. The results of nonlinear static analysis showed that during work of the engine with maximum power the high stress area was located in crack initiation zone. Based on results of performed investigations it was concluded that the main reason of premature fatigue failure was high-cycle fatigue of the material in external zone of the crank pin where the small structural radius was designed. In final part of the work the recommendations for increase of the fatigue life of analyzed crankshaft were formulated. Highlights: In a diesel engine the failure of the crankshaft was occurred. The crack origins were not covered by material defect and corrosion products. Results of numerical analysis showed that large stresses were observed in the fillet of the crank pin. The failure of the crankshaft was caused by the high-cycle fatigue. The crack initiation was accelerated by bad hardening process of pin area and improper chemical composition of the material.